2006
DOI: 10.3748/wjg.v12.i5.815
|View full text |Cite
|
Sign up to set email alerts
|

Small gastrointestinal stromal tumor concomitant with early gastric cancer: A case report

Abstract: The term gastrointestinal stromal tumors (GISTs) is defined diagnostically as the main group of mesenchymal tumors with spindle or epithelioid cells arising from the wall of the gastrointestinal tract with immunohistochemical reactivity for CD117 antibody. Previous studies revealed that cells in GISTs express a growth factor receptor with tyrosine kinase activity (termed c-kit), which is the product of the c-kit proto-oncogene. The most specific and practical diagnostic criteria for GISTs are: immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 10 publications
1
24
0
3
Order By: Relevance
“…It was reported that H pylori are related to the pathogenesis of gastric carcinoma and mucosaassociated lymphoid tumor [5,6] . We previously reported a case of a 0.4-cm GIST concomitant with an early gastric cancer in 2005 [7] , and between 2003 and 2007, we intermittently detected one case of multiple 0.2-cm to 0.5-cm gastric neuroendocrine tumors and additional 5 cases of 0.4-15 cm gastric GISTs. All except for 2 of the cases yielded positive CLO tests.…”
Section: Discussionmentioning
confidence: 78%
“…It was reported that H pylori are related to the pathogenesis of gastric carcinoma and mucosaassociated lymphoid tumor [5,6] . We previously reported a case of a 0.4-cm GIST concomitant with an early gastric cancer in 2005 [7] , and between 2003 and 2007, we intermittently detected one case of multiple 0.2-cm to 0.5-cm gastric neuroendocrine tumors and additional 5 cases of 0.4-15 cm gastric GISTs. All except for 2 of the cases yielded positive CLO tests.…”
Section: Discussionmentioning
confidence: 78%
“…Alternatively, local resection should be performed. [10][11][12] Owing to the presence of incidental GIST, 5 (45%) patients with primary epithelial malignancies in our series required additional procedures intraoperatively. Simple excision or wedge resection was performed in all cases involving the eventual gastric conduit used to restore intestinal continuity.…”
Section: Discussionmentioning
confidence: 99%
“…Simple coincidence appears to be the most likely explanation, although gene mutations or neighboring gastric tissues affected by the same carcinogen are other hypotheses reported in the literature (2,11,12). A combined genetic deregulation appears to be involved in the pathogenesis of these two entities.…”
Section: Discussionmentioning
confidence: 85%